1997
DOI: 10.1007/s004180050123
|View full text |Cite
|
Sign up to set email alerts
|

Lysozyme expression in the rat parotid gland: light and electron microscopic immunogold studies

Abstract: Lysozyme (muramidase) is capable of direct bacteriolytic action by hydrolyzing glycosidic bonds in bacterial cell walls. Although it is broadly distributed in vertebrate tissues and secretions, the cellular and subcellular localizations of the enzyme are still not well known. The present study examines the distribution of lysozyme expression in the various cell types of LR gold-embedded rat parotid gland, applying a postembedding immunogold-silver staining technique for light microscopy. Simultaneously, a post… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The expression and/or secretion of salivary components, which include antimicrobial substances, such as lysozyme, lactoperoxidase, lactoferrin, immunoglobulin A, and β-defensins, and glycoconjugates, such as mucin glycoproteins, as well as digestive enzymes such as α-amylase and lingual lipase, 41,42 have been substantially demonstrated in the salivary glands of humans, 3,[43][44][45][46][47][48] rodents, 36,49,50 and goats. [51][52][53] Meanwhile, the expression of antimicrobial substances differed among glands, with high expressions of lysozyme in the parotid and zygomatic glands and lactoperoxidase in the parotid gland.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The expression and/or secretion of salivary components, which include antimicrobial substances, such as lysozyme, lactoperoxidase, lactoferrin, immunoglobulin A, and β-defensins, and glycoconjugates, such as mucin glycoproteins, as well as digestive enzymes such as α-amylase and lingual lipase, 41,42 have been substantially demonstrated in the salivary glands of humans, 3,[43][44][45][46][47][48] rodents, 36,49,50 and goats. [51][52][53] Meanwhile, the expression of antimicrobial substances differed among glands, with high expressions of lysozyme in the parotid and zygomatic glands and lactoperoxidase in the parotid gland.…”
Section: Discussionmentioning
confidence: 99%
“…Lysozyme was strongly expressed in canine parotid and zygomatic glands. Lysozyme expression in the rat parotid gland has been reported immunohistochemically 36 ; however, the expression level of lysozyme could not be compared by immunoblotting because the primary antibody used in this study reacts with canine protein but not with rat protein. The expression level of α-SMA, a marker for myoepithelial cells, 37 was relatively strong in the canine tissues, suggesting the probable association between secretory function and muscular contraction.…”
Section: Expression Of Secretory Proteins In Canine Salivary Glandsmentioning
confidence: 92%
“…The associations between extreme age and oral antimicrobial factor concentrations reported here may be due to age-related changes in specific cell types that produce these factors within glandular tissues. SLPI and lysozyme are synthesized and secreted mainly by serous acinar cells within major and minor salivary glands [29,[37][38][39]. Lactoferrin is produced primarily in ductal cells, stromal cells and, to a lesser degree, acinar cells of salivary glands [5,37,40].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the existence of more than one population of mature secretory granules in parotid acinar cells in terms of their different matrix electron density configuration (Hand, 1972;Pinkstaff, 1980Pinkstaff, , 1993Simson et al, 1974;Tandler and Phillips, 1993). Such a polymorphic picture is generally accepted to be a direct reflection of the segregation of many of the major constituents of granules in specific areas of their matrix, as demonstrated by several immunocytochemical studies in mammalian salivary glands which showed a characteristic heterogeneous compartmentalization within the granule for different molecules, such as α-amylase, agglutinin and proline-rich proteins (Mansouri et al, 1992;Matsuura and Hand, 1991;Marchetti et al, 2000;Staneva-Dobrovski, 1997;Takano et al, 1991Takano et al, , 1993Vugman and Hand, 1995).…”
Section: Introductionmentioning
confidence: 98%